Optimize Hermetia illucens Small-scale Growing Conditions for Treating Organic Municipal Solid Waste - Ha, Nguyen Thi Thu; Ngoc Thuan, Le (VNU Journal of Science: Earth and Environmental Sciences, 2025)
Currently, rapid urbanization has led to a significant increase in municipal solid waste (MSW), especially the organic waste component (OWC), which accounts for a high proportion and often leads to unpleasant odors, leachate, insects, and pathogenic bacteria spread. Research on proper treatment of this component not only helps address environmental pollution but also generates many high-value economic products. The Hermetia illucens is considered a potential biological solution due to its ability to quickly decompose OWC, while producing nutrient-rich larvae, also known as calcium worms. These larvae can be used in animal feed or organic fertilizer production. Many non-governmental organizations and investment funds supporting circular agriculture models using Hermetia illucens to treat OWC are being researched and tested, and some factories have recently been built in Vietnam. The use of household OWC to grow Hermetia illucens on a small scale helps manage organic waste at the source and contributes to a circular economy, and being environmentally friendly. This study tested four ssmall-scale OWC treatment: OWC, OWC mixed with protein, OWC with microbial product, and OWC both mixed with protein and microbial product under four different climatic and temperature conditions. The study identified the optimal conditions for the development of Hermetia illucens as a warm and humid temperature of about 28–35 °C, humidity around 60-75%, with food sources being the organic components in OWC supplemented with nitrogen to achieve a C/N ratio of about 25-30:1, and microbial supplements mixed in to quickly decompose and soften the food so that calcium insects can utilize it, while also limiting unpleasant odors.